Data-Driven Coastal Nutrients Estimation: Current Status, Research Gaps, and Future Developments - Sihan Ni; Jin Qi; Xiangbin Ran; Zhiqiang Liu; Sensen Wu; Minyu Wang; Keyi Yang; Chengfeng Le; Zhenhong Du (Water Research, 2026)

Application of Bi2MoO6 materials in ammonia synthesis through photocatalytic nitrogen fixation - Ping Zhang; Xinyu Du; Keyi Chai; Jiaqi Guo; Lu Zhang; Xiaoping Su; Lianbiao Zhao (Journal of Environmental Chemical Engineering, 2026)

Accurately tracking radial location dynamics of freeze-thaw front in tree stems under field conditions: a comprehensive model considering non-uniformity of stem water content distribution and electric-field attenuation of electromagnetic sensor - Yuxin Liu; Xiaofei Yan; Taisheng Du; Ricardo F. de Oliveira; Keyi Zhang; Qiang Cheng (Agricultural and Forest Meteorology, 2026)

Enhanced buoy-based water quality time series imputation in coastal waters - Minyu Wang; Keyi Yang; Junyu He; Jin Qi; Yijun Chen; Haoqi Gu; Renyi Liu; Sensen Wu; Zhenhong Du (Journal of Hydrology, 2025)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

Synergistic effects of nanoplastics and graphene oxides on microbe-driven litter decomposition in streams - Yao Wang; Keyi Wang; Junbo Yang; Mingquan Dai; Danjuan Zeng; Xiaohui Wang; Jingjing Du; Gaozhong Pu (Journal of Hazardous Materials, 2025)

Four years of air exposure: Passive surface chemical engineering to improve the stability and photoluminescence performance of CsPbBr3 perovskite quantum dot glass - Yongmin Duan; Shugang Li; Keyi Gu; Zhaojing Kuang; Juan Du; Junjie Zhang (Chemical Engineering Journal, 2025)

The mechanistic insights and therapeutic implications of sheepskin collagen peptide as a novel anti-photoaging agent - Baifeng Fu; Keyi Zhou; Hui Yao; Ximing Yang; Xiaoyu Ma; Qi Yang; Shuzhen Cheng; Ming Du (Food Bioscience, 2024)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

Proposal and application of onshore lattice wind turbine support structure and integrated multi-scale fatigue assessment method - Chuannan Xiong; Kaoshan Dai; Yuxiao Luo; Zufei Yang; Keyi Qiu; Hang du; Xiao Tang (Engineering Structures, 2024)

Attentional impairment and altered brain activity in healthcare workers after mild COVID-19 - Keyi Lin; Yaotian Gao; Wei Ji; Yan Li; Wei Wang; Mengcheng Du; Jia Liu; Zhengyu Hong; Tao Jiang; Yuyang Wang (Brain Imaging and Behavior, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is highly transmissible and pathogenic. Patients with mild cases account for the majority of those infected with coronavirus disease 2019 (COVID-19). Although there is evidence that many patients with COVID-19 have varying degrees of attentional impairment, little is known about how SARS-COV-2 affects attentional function. This study included a high-risk healthcare population divided into groups of healthcare workers (HCWs) with mild COVID-19 (patient group, n = 45) and matched healthy HCWs controls (HC group, n = 42), who completed general neuropsychological background tests and Attention Network Test (ANT), and underwent resting-state functional magnetic resonance imaging (rs-fMRI) using amplitude of low-frequency fluctuation (ALFF) to assess altered brain activity; Selective impairment occurred in orienting and executive control networks, but not in alert network, in the patient group, and widespread cognitive impairment encompassing general attention, memory, and executive dysfunction. Moreover, the patient group had significantly lower ALFF values in the left superior and left middle frontal gyri than the HC group. SARS-COV-2 infection may have led to reduced brain activity in the left superior and left middle frontal gyri, thus impairing attentional orienting and executive control networks, which may explain the development of attentional deficits after COVID-19.

Environment relevant exposure of perfluorooctanoic acid accelerates the growth of hepatocellular carcinoma cells through mammalian target of rapamycin (mTOR) signal pathway - Jiawei Hong; Xiaoyan Wang; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Keyi Du; Diyu Chen; Shusen Zheng; Linping Cao (Environmental Pollution, 2024)

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)